Pygo2+ T cells possess immunosuppressive features and inferior immunotherapeutic response in gastric cancer - Chang, Weilong; Yan, Huifang; Zhang, Yawei; Sang, Zibo; Bu, Bei; Deng, Rui; Li, Kaibo; Li, Jiajing; Fu, Yang; Cui, Jinyuan (Frontiers in Immunology, 2025)
BackgroundGastric cancer (GC) poses a significant threat to human health. Despite considerable advancements in immunotherapy for GC, the effectiveness of current immunotherapeutic targets remains constrained by the heterogeneity of the tumor microenvironment and mechanisms of immune evasion. Consequently, the identification of novel immunotherapy targets has emerged as a critical area of research. This study investigates the potential of Pygo2 as a target for immunotherapy in GC.MethodsThe expression and cell localization of Pygo2 in GC tissues were characterized by single cell sequencing, flow cytometry and mIHC. The relationship among Pygo2 expression and prognosis, immune microenvironment and immunotherapy effect was studied in 282 gastric cancer patients.ResultsThe findings indicate a significant upregulation of Pygo2 expression in GC tissues, particularly within tumor cells and T cells. Pygo2 expression in T cells is not only correlated with the advanced T stage and N stage but also inversely associated with patient survival. Additionally, overexpression of T cell Pygo2 resulted in a significant increase in TCF7, which suggested Pygo2+ T cells might represent a subset of exhausted T cells. The study also demonstrated that the density of Pygo2+ CD8+ T cells is negatively correlated with the efficacy of immunotherapy.ConclusionTumor-infiltrating Pygo2+ T cells could be applied as a clinical prognosticator and a predictive biomarker for immunotherapy responsiveness to GC. These findings offer new therapeutic targets for the treatment of GC and provide fresh insights into cancer treatment strategies.